2020
DOI: 10.1515/ijfe-2019-0189
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reaction parameters on the non-enzymatic browning reaction between l-ascorbic acid and glycine

Abstract: The non-enzymatic browning (NEB) reaction between l-ascorbic acid (ASA) and glycine (Gly), including the effects of temperature (110–150 °C), time (10–150 min) and pH (4.5, 6.8, 8.0 and 9.5) on the formation of un-colored intermediate products (UIPs), browning products (BPs) and volatile products (VPs), were investigated. The results showed that pH had a remarkable effect on the reaction. The characteristics of zero-order kinetics for the formation of UIPs and BPs were discussed, and the corresponding activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The effect of temperature on the degradation of ASA was obvious. The degradation rate of ASA was faster ( 5 , 9 , 30 , 35 ). The concentration of ASA decreased as the reaction time elapsed; the concentration of ASA reached equilibrium within the long reaction time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of temperature on the degradation of ASA was obvious. The degradation rate of ASA was faster ( 5 , 9 , 30 , 35 ). The concentration of ASA decreased as the reaction time elapsed; the concentration of ASA reached equilibrium within the long reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…As ASA was the only initial compound present at the time (t) zero in the solution loaded in the closed reactor, it was the only compound whose concentration was measured during the reaction. The following chemical equation can be written as Formula A ( 5 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, further increment of the frying temperature to 180 °C and 200 °C resulted in slight intensification of the color difference (Tukey's test, p < 0.01). This suggested that the ACD of the deep-fried eggplant might be related to non-enzymatic browning, which was confirmed to be strongly associated with L-ascorbic acid (vitamin C) loss during the thermal process (Yang et al, 2021). Eggplant contains a moderate amount of L-ascorbic acid, with an average quantity of 89 mg/100g (Hanson et al, 2006).…”
Section: Effects Of Frying Conditionsmentioning
confidence: 85%